Literature Review on the Relationship Between Hearing Impairment and Obesity - Lalusu, Regita Geiananti Y.; Pontoh, Israwati; Masiti, Masiti; Wijayanti, Anik; Sudirman, Sudirman; Yani, Ahmad; Amalinda, Finta (PROMOTOR, 2025)
Hearing loss is a global health problem that can affect aspects of an individual's life, both physically, psychologically and socially. The prevalence of hearing loss continues to increase, particularly in the adult and elderly population. On the other hand, obesity is also a significant public health problem with increasing prevalence in various countries, including Indonesia. Obesity not only affects the cardiovascular system and metabolism, but also has the potential to affect sensory organs, including hearing. This study aims to determine whether there is an association between obesity and hearing loss. This study was conducted in the form of a literature review using the Prisma method using three databases, namely Google Scholar, PubMed, Sciencedirect. The literature to be used must be in English and/or Indonesian, within the last 10 years (2014), and fully accessible. Based on the results of 10 studies, it was found that obesity may increase the risk of hearing loss. In conclusion, obesity is associated with an increased risk of hearing loss. In addition, comorbidities caused by obesity play an important role in the mechanism of hearing loss.